2022
DOI: 10.1088/1757-899x/1249/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistive behaviour of ternary Cu-based materials processed by high-pressure torsion

Abstract: Severe plastic deformation using high-pressure torsion of ternary Cu-based materials (CuFeCo and CuFeNi) was used to fabricate bulk samples with a nanocrystalline microstructure. The goal was to produce materials featuring the granular giant magnetoresistance effect, requiring interfaces between ferro- and nonmagnetic materials. This magnetic effect was found for both ternary systems; adequate subsequent annealing had a positive influence. The as-deformed states, as well as microstructural changes upon thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[121,122] Binary and ternary powder mixtures consisting of different compositions of elemental Cu, Co, Ni and Fe were thus processed by HPT-deformation and examined as possible candidates for the granular GMR effect. [123][124][125] In these studies, it could be shown that it is possible to produce HPTdeformed samples showing GMR behavior at room temperature. The GMR-ratio is small compared to multilayer systems already in application.…”
Section: Hpt-deformation Of Powders To Obtain Soft Magnetic Materialsmentioning
confidence: 99%
“…[121,122] Binary and ternary powder mixtures consisting of different compositions of elemental Cu, Co, Ni and Fe were thus processed by HPT-deformation and examined as possible candidates for the granular GMR effect. [123][124][125] In these studies, it could be shown that it is possible to produce HPTdeformed samples showing GMR behavior at room temperature. The GMR-ratio is small compared to multilayer systems already in application.…”
Section: Hpt-deformation Of Powders To Obtain Soft Magnetic Materialsmentioning
confidence: 99%